Resurrecting Empire : western footprints and America's perilous path in the middle east - Khalidi, Rashid (Boston : Beacon Press, 2004)
"Begun as the United States moved its armed forces into Iraq, Rashid Khalidi's book examines the record of Western involvement in the region and analyzes the likely outcome of our most recent Middle East incursions. Drawing on his encyclopedic knowledge of the political and cultural history of the entire region as well as interviews and documents, Khalidi paints a chilling scenario of our present situation and yet offers a tangible alternative that can help us find the path to peace rather than Empire."--BOOK JACKET.
Includes bibliographical referencesand index.
Keywords: Democracy -- Middle East; Arab-Israeli conflict; Middle East -- Relations -- United States; United States -- Relations -- Middle East